La demarcación territorial distrital en la cuenca del río Omas (Asia) - Comeca Chuquipul, Miguel Angel (2010)
The territory of the Peru according to the political constitution in use, you split into regions, departments, provinces and districts. However the majority of them lack definite limits and indefinition as to the categories of the populated centers, this situation has generated in some cases conflicts between populations placed in bordering areas, deficiency of state presences in the fringe benefit of services, as well as Territorial quarrels. Present investigation takes like unit of analysis the districts the fact that they form splits of a geographic named unit basin hydrographic of the river Omas. The purpose is to evaluate the situation of his limit distritales, identifying possible areas of conflict, diagnosing the categories of his populated centers, determining as the role that the competent institutions in this subject and to propose keep is alternatives of solution to the problems.